2012
DOI: 10.1093/geronb/gbs044
|View full text |Cite
|
Sign up to set email alerts
|

Threat or Boost? Social Comparison Affects Older People's Performance Differently Depending on Task Domain

Abstract: The research demonstrates that a threatening comparison can result in underperformance by older people both in negatively and positively self-stereotyped task domains. It also demonstrates that social comparison with younger people can enhance older people's performance in a positively stereotyped task domain. The implications for creating circumstances likely to enable older people to achieve their full potential are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 39 publications
7
56
1
5
Order By: Relevance
“…The positive finding from an intervention perspective is that not only negative but also positive stereotype activation tends to persist over time. This is consistent with other evidence that stereotypes can also be deployed positively to "boost" older people's performances and motivation in a more long-lasting manner (Swift, Abrams, & Marques, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…The positive finding from an intervention perspective is that not only negative but also positive stereotype activation tends to persist over time. This is consistent with other evidence that stereotypes can also be deployed positively to "boost" older people's performances and motivation in a more long-lasting manner (Swift, Abrams, & Marques, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Swift et al [61] examined the performance of older adults in a domain where they are stereotyped more favorably than younger people (via crossword puzzles). They found that, compared with the control condition, the enhancing social comparison boosted performance among the older adults [61].…”
Section: Explicit Priming Of Positive Stereotypes Of Aging (And Sterementioning
confidence: 99%
“…Although explicitly making people feel favorable compared to younger people in experimental studies has shown short-term improvements in physical [62] and cognitive [61] tasks, respectively, longer-term effects of explicit positive stereotypes in the daily lives of older adults (such as media messages depicting "healthy, active, and happy" older people) and the effects of dominant "successful aging" discourses (found in academic literature and popular press) are less well known. Making upward, rather than downward, social comparisons has multiple likely effects on the health behaviors of older individuals [63].…”
Section: Explicit Priming Of Positive Stereotypes Of Aging (And Sterementioning
confidence: 99%
“…paradox of wellbeing, Swift et al 2013;Whitbourne and Sneed 2002). Research suggests a positive age-identity is one mechanism by which older adults are able to maintain positive self-esteem, sense of self and wellbeing.…”
Section: Age Identificationmentioning
confidence: 99%
“…For instance, research from the US, UK and across Europe has continued to suggest that older people are stereotyped as frail, ill, dependent and incompetent (Levy 2009;Marques et al 2014b, Coudin andAlexopoulos 2010), but also wise, experienced and more moral than younger adults (Levy 1996;Swift et al 2013;Abrams et al 2011a). Several studies have explored age-related stereotypes across age and cultural groups.…”
Section: Age Stereotypesmentioning
confidence: 99%